Association between adolescent smoking and subsequent college completion by parent education – A national longitudinal study. (1st April 2022) - Ajith, Aniruddh; Temmen, Chelsie; Haynie, Denise; Choi, Kelvin
Abstract: Background: Educational attainment is a social determinant of health associated with better quality of life and health outcomes. Current understanding of the association between adolescent smoking and college completion is limited. This study examined the association between adolescent smoking and subsequent college completion and how it varied by parent education in a longitudinal study of U.S. adolescents followed into young adulthood. Methods: Data were collected annually from a nationally representative cohort of 10th graders who participated in the NEXT Generation Health Study (2009 −2017; N = 1407). Participants reported if they smoked during 10th-12th grades (2009–2013). Self-report college completion was assessed in 2017. Parent reported their educational attainment at baseline. Weighted logistic regression models were used to assess the association between adolescent smoking during 10th-12th grades and subsequent college completion in the entire sample and stratified by parent educational attainment, adjusting for demographics, depressive symptoms, alcohol use, and parental monitoring. Results: Overall, adolescents who smoked during 10th-12th grade had lower odds of subsequently completing college compared to those who did not smoke (AOR=0.33, 95%CI=0.20–0.57). This association was stronger among those whose parents had ≤high school education (AOR=0.08, 95% CI=0.02–0.31) and some college education (AOR=0.18, 95%CI=0.08–0.39). Discussion: Adolescents from lower educational attainment households showed disproportionately stronger association between adolescent smoking and subsequent college completion. Future research needs to determine whether and how strategies to reduce adolescent smoking may promote educational attainment especially among adolescents whose parents have less than a college education. Highlights: Educational attainment is a social determinant of health. We found that adolescent smoking was related to lower odds of a college completion. This association was stronger among those whose parents were without a college education. Addressing adolescent smoking may promote higher educational attainment.